Collecting and communicating perishable data in a post-disaster context: rapid research and rapid dissemination - Gorbea Díaz, Laura; Chopel, Alison; Fernós Sagebién, Antonio; Bonilla Marrero, Lorena; Rivera Figueroa, Gerardo; Pecci Zegrí, Nicole; Cardona, Anohiska; Mulero Oliveras, Juneilis; La Santa, Luis; Sánchez Rey, Paola (Frontiers in Sociology, 2023)
Context: Puerto Rico experienced four disasters between 2017 and 2021: two Hurricanes, thousands of earthquakes reaching 6.4 magnitude, and the COVID-19 pandemic. In this context, our team sought to understand the impact of disaster aid distribution on poverty and economic inequality, and how each of those shaped the distribution of COVID-19 across Puerto Rico. Rapid research was required to ensure we could collect perishable data within this ever-changing context. Challenges: Our mixed methods design relied on secondary and primary data. Because analyses of the former were to inform where and how to collect the latter, timing was essential. Challenges in accessing secondary data resulted in unexpected delays. Rapid primary data collection generated tensions as the team worked around compounding traumas experienced by participants, heightened risk for re-traumatization and fatigue, the risk of COVID-19, the digital divide, and intermittent electrical and telecommunication services. Adaptations: In response to the delayed access to secondary data, we adjusted our research question. We continued to collect data as they became available, incorporating some immediately into analyses, and cleaning and storing others for future research opportunities. To overcome ongoing trauma challenges and prevent fatigue, we recruited and hired a large temporary team, including members of communities where we collected data. By recruiting participants and co-researchers at the same time and place, we both collapsed time between these activities and increased our team’s contextual competency. Lessons: Rapid research requires agility. Working within a convergence framework to investigate wicked problems had the unexpected benefit of providing varied disciplinary approaches which supported adaptation to changing conditions in the field. Collecting and analyzing data iteratively and utilizing local resources enable rapid research that was rigorous and yielded rich data. Contributions: Our team combined member-checking with community-level dissemination, enabling us to hone findings further before presenting to policy makers and media. Rapid research creates opportunities to make data-informed program and policy adjustments when they can be most impactful. The more rapid research we do, the better we will get at it, and the more accustomed community leaders, policy makers and program designers will become to using data to inform decisions.